2020
DOI: 10.4102/sajpsychiatry.v26i0.1553
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life amongst nurses in psychiatric observation units

Abstract: Background: Professional quality of life amongst nurses in psychiatric observations units may be affected by working conditions such as an overflow of mental health care users (MHCUs), a shortage of nurses, lack of specialised staff and inadequate infrastructure to accommodate MHCUs amongst others.Aim: The aim of the study was to investigate the professional quality of life amongst nurses in psychiatric observation units.Setting: The study was conducted in psychiatric observation units in eight hospitals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…They are seen together with the adults and youth in the general wards. Studies have shown that nurses with specialist training are better equipped to render care to patients [ 19 , 20 ]. Looking at the curriculum of most nursing schools, gerontology is usually not a stand-alone course [ 12 , 15 , 29 ] but students are expected to learn it in their medical-surgical nursing classes.…”
Section: Introductionmentioning
confidence: 99%
“…They are seen together with the adults and youth in the general wards. Studies have shown that nurses with specialist training are better equipped to render care to patients [ 19 , 20 ]. Looking at the curriculum of most nursing schools, gerontology is usually not a stand-alone course [ 12 , 15 , 29 ] but students are expected to learn it in their medical-surgical nursing classes.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 12 studies included, three studies were dissertations. Two studies were conducted in America (Boisseau et al, 2019; Monroe, 2008) and one each from England (Foster, 2019), Italy (Franza et al, 2015), Israel (Itzhaki et al, 2018), Norway (Lauvrud et al, 2009), Japan (Kobayashi et al, 2020), South Africa (Maila et al, 2020), Greece (Mangoulia et al, 2015), Canada (Murray, 2019), Iran (Tirgari et al, 2019) and China (Xie et al, 2020). Publication years range from 2008 to 2020 with ten studies published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Xie et al (2020) reported moderate levels of CF with moderate results for CS, BO and STS. Murray (2019) and Maila et al (2020) reported moderate to high levels of risk for CF. Murray (2019) reported 49.1% moderate CF and 22.4% high CF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las definiciones de agotamiento con mayor frecuencia apuntan a estresores ambientales, mientras que las definiciones de fatiga por compasión abordan la naturaleza relacional de la condición. Además, el agotamiento se asocia con sentimientos de desesperanza y apatía y crea una incapacidad para desempeñar sus tareas de manera efectiva (Mashego, 2016;Maila, Martin & Chipps, 2020); en cambio, la fatiga por compasión está más vinculada a la empatía (Hidalgo, Martínez & Carrasco, 2018). El agotamiento y la fatiga por compasión pueden convertirse en cargas abrumadoras en enfermeras/ os, y causar problemas físicos, mentales y emocionales, al igual que dificultades en la salud (Hunsaker, 2015).…”
Section: Introductionunclassified